2019
DOI: 10.1016/j.jpainsymman.2019.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the French Version of the Integrated Palliative Care Outcome Scale

Abstract: Context. The Integrated Palliative care Outcome Scale (IPOS) is a widely used tool for assessing patient needs in palliative care. Objectives. The aim of this study is to provide a validated version of the patient and staff IPOS for French-speaking Switzerland (IPOS-Fr) and assess its psychometric properties. Methods. The validation took place in 12 palliative care units and mobile teams. At baseline (T1) and three days later (T2), patients' general health status, palliative care needs (IPOS-Fr) and quality of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 10 publications
5
25
1
1
Order By: Relevance
“…This might be because FACT-G Physical Wellbeing subscale includes items about the emotional effects of physical problems, such as "I am bothered by the side effects of treatment", which is similar to items in the IPOS Emotional Symptoms subscale, such as "Have you been feeling anxious or worried about your illness or treatment?" The IPOS Communication and Practical Issues subscale had poor correlation with all FACT-G and ESAS-r scores, echoing ndings in other IPOS validation studies (5,8,9). The consistently poor correlation between this subscale and other PROMs suggests that the types of problems in this Communication and Practical Issues subscale are not measured by existing PROMs.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…This might be because FACT-G Physical Wellbeing subscale includes items about the emotional effects of physical problems, such as "I am bothered by the side effects of treatment", which is similar to items in the IPOS Emotional Symptoms subscale, such as "Have you been feeling anxious or worried about your illness or treatment?" The IPOS Communication and Practical Issues subscale had poor correlation with all FACT-G and ESAS-r scores, echoing ndings in other IPOS validation studies (5,8,9). The consistently poor correlation between this subscale and other PROMs suggests that the types of problems in this Communication and Practical Issues subscale are not measured by existing PROMs.…”
Section: Discussionsupporting
confidence: 52%
“…That IPOS showed overall good measurement properties in both English and Chinese with good construct validity, internal consistency and test-retest reliability suggests that IPOS could be used as a screening tool to identify patients with problems or concerns that could trigger a referral to the specialist palliative care team (20). The IPOS tool could also be used to characterise the pro le of palliative care concerns in the wider population of patients with advanced cancer, regardless of whether they are referred to palliative care services or not (21) There was poor patient-staff agreement in both languages when used in this study population, unlike other studies (5,8). This could be because majority of the staff included in this study were ward nurses in the acute hospital setting, who may be less attuned to the patient's problems and concerns compared to palliative care clinicians surveyed in the other validation studies.…”
Section: Discussionmentioning
confidence: 91%
“…IPOS was found to have excellent reliability [12][13][14][15][16] and face and content validity was also confirmed in several studies using cognitive interviews [11,17,18] Convergent validity has been confirmed for the original and German IPOS [13], Japanese version of IPOS [14] and French IPOS [16]. In many other countries the process of validation is ongoing and all language version which are currently available, such as Portuguese, Polish, Greek etc., can be found online (www.pos-pal.org).This study aims to provide a valid version of IPOS in Czech and to report the psychometric properties of IPOS from this first pilot Czech study.…”
Section: Introductionmentioning
confidence: 90%
“…IPOS was found to have excellent reliability (12)(13)(14)(15)(16) and face and content validity was also confirmed in several studies using cognitive interviews (11,17,18) Convergent validity has been confirmed for the original and German IPOS (13), Japanese version of IPOS (14) and French IPOS (16). In many other countries the process of validation is ongoing and all language version which are currently available, such as Portuguese, Polish, Greek etc., can be found online (www.pos-pal.org).This study aims to provide a valid version of IPOS in Czech and to report the psychometric properties of IPOS from this first pilot Czech study.…”
Section: Introductionmentioning
confidence: 82%